INTEGRASI STEM DAN DIGITAL LEARNING DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Lindayani Lindayani; Nurul Zikri Filina; Dian Erlita; Febry Fahreza; Nurjannah; Syah Mohd Hadiid Thaariq (Jurnal Genta Mulia, 2026)
This study aims to analyze the implementation of the integration of the STEM (Science, Technology,Engineering, Mathematics) approach and digital learning in strengthening the integration of theSTEM (Science, Technology, Engineering, Mathematics) approach and digital learning in the sciencesubject in elementary schools and its impact on improving students' critical thinking skills. This studyuses a qualitative approach by studying and analyzing books and relevant reference sources. Data wereobtained from various appropriate scientific sources and analyzed descriptively. The study shows thatcombining STEM education with digital learning can increase student participation, help theirunderstanding of concepts, and train 21st-century skills such as critical thinking, creativity, collaboration, and communication skills. This integration is a creative solution in the science learning process in today's increasingly digital era.